2007
DOI: 10.1128/jvi.00783-07
|View full text |Cite
|
Sign up to set email alerts
|

Murine Noroviruses Comprising a Single Genogroup Exhibit Biological Diversity despite Limited Sequence Divergence

Abstract: Viruses within the genus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
385
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 243 publications
(412 citation statements)
references
References 81 publications
13
385
1
13
Order By: Relevance
“…However, due to the lack of an efficient cell culture or animal model, direct evaluation of human NoV serotypes remains challenging. The most widely used MNV surrogate model exhibits little genetic and antigenic variation and all laboratory strains belong to the same serotype (Thackray et al, 2007).…”
Section: Antigenic Diversity and Serotypesmentioning
confidence: 99%
“…However, due to the lack of an efficient cell culture or animal model, direct evaluation of human NoV serotypes remains challenging. The most widely used MNV surrogate model exhibits little genetic and antigenic variation and all laboratory strains belong to the same serotype (Thackray et al, 2007).…”
Section: Antigenic Diversity and Serotypesmentioning
confidence: 99%
“…ORF-1 encodes the non-structural proteins, whereas ORF-2 and ORF-3 encode structural proteins (Sosnovtsev et al, 2006). ORF-4 was recently identified within the MNV-1 genome and encodes a single protein of unknown function (Thackray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, MNV infection does not show any clinical symptoms in immunocompetent mice [23], except for occasional association with histopathological changes in the intestine and the spleen [14]. On the other hand, it sometimes induces noticeable symptoms such as diarrhea in immunodeficient mice, such as OTI/Rag1 -/-IFN-g -/-and b 2 M -/-mice [20]. Persistent MNV infection has been reported in not only immunodeficient but also immunocompetent mice [4,6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis of this agent has revealed that the pathogen (MNV-1) is close--Original-ly related to human norovirus, a member of the Caliciviridae family of positive-strand RNA viruses. In addition to MNV-1, several MNV strains have been isolated from laboratory mice [6,10,20]. Generally, MNV infection does not show any clinical symptoms in immunocompetent mice [23], except for occasional association with histopathological changes in the intestine and the spleen [14].…”
Section: Introductionmentioning
confidence: 99%